A aspartil aminopeptidase APE4 contribui para os atributos de virulência em Cryptococcus neoformans - Gontijo, Fabiano de Assis [UNIFESP] (2016)
Cryptococcus neoformans is an opportunistic pathogenic fungus of human beings that infects mainly immunocompromised patients. When left untreated can lead to death and due to similarities between fungal cells and animals, antifungal compounds available to treat mycoses are limited and usually result in toxicity to the host. Still, literature brings reports of clinical and environmental strains with antifungal resistance of canonical usage. This limitation takes investigators to extend the knowledge on the biology of pathogenic fungi in search of new therapeutic targets and drugs. Therefore, Dr. Marcelo A. Vallim generated a mutant library by random inserting a cassette that confers resistance to neomycin that was mediated by Agrobacterium tumefaciens that aim was to identify mutants unable to grow on mammalian physiological temperature (37°C). This mutant library was described by de Gontijo et al. (2014). Among the various mutants sensitive to 37°C, we identified one with the interruption in the APE4 gene that encodes the protein aspartyl aminopeptidase. In Saccharomyces cerevisiae, the metalloproteinase family M18 Ape4 is activated by nitrogen deprivation. This protein is involved in Autophagy, and also part of the pathway of transport cytoplasm to vacuole targeting (CVT) along with proteins, Atg11 and Ams1 Ape1, Atg19. The lack of Ape4 protein in S. cerevisiae does not prevent growth to high temperature, however, in C. neoformans the ape4 mutant does not grow at 37°C, produces less melanin and features lower capsular volume at 30°C and 37°C. The ape4 strain features increased sensitivity to antifungal fluconazole and lower survival within macrophages (p<0.05) when compared with wild strains (KN99) and reconstituted (ape4 + APE4), yet, the ape4 mutants are avirulent in animal model. The experiments with fusion protein GFP